2016
DOI: 10.1021/acs.jpcc.6b08427
|View full text |Cite
|
Sign up to set email alerts
|

Highly Sensitive Ultraviolet Light Sensor Based on Photoactive Organic Gate Dielectrics with an Azobenzene Derivative

Abstract: Photochromic molecules have been recently adopted by many researchers for organic field-effect transistor (OFET) applications, since they offer the opportunity to achieve flexible-type ultraviolet (UV) light sensors with the advantages of organic material-based solution processes. Here, we present the novel usage of an azobenzene derivative in the gate dielectric layer of an OFET for highly sensitive and reliable UV sensing applications. Owing to the large change of capacitance caused by the reversible photois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 35 publications
1
30
0
Order By: Relevance
“…This F matrix is similar to the F matrices used in other contracted basis calculations for [53,69], CH 4 [67], CH + 5 [68]. All these F matrices have indices that label eigenfunctions of a Hamiltonian that depends on a subset of the coordinates (here…”
Section: If One Evaluatesvmentioning
confidence: 92%
“…This F matrix is similar to the F matrices used in other contracted basis calculations for [53,69], CH 4 [67], CH + 5 [68]. All these F matrices have indices that label eigenfunctions of a Hamiltonian that depends on a subset of the coordinates (here…”
Section: If One Evaluatesvmentioning
confidence: 92%
“…Following preliminary estimations of Fleurat-Lessard et al [54], this "reef" feature was incorporated into a so-called "hybrid PES" by Babikov et al [38] by introducing a 1D semiempirical correction to the three-dimensional Siebert-Schinke-Bittererova (SSB) [44,45] PES with empirical adjustments to match the experimental dissociation energy. This modified mSSB surface containing a shallow van der Waals (vdW) minimum along the dissociation reaction coordinate around r 1 ∼ 4.5−5.0 a 0 has been used to study the metastable states [38] and also suggested the existence of van der Waals bound states [55][56][57][58]. A detailed review of ozone investigations up to this stage has been presented in the "Status report of the dynamical studies of the ozone isotope effect" by Schinke et al [1] who concluded that the calculated rate constants were about 3-5 times smaller than the measured ones and had a wrong temperature dependence.…”
Section: Introductionmentioning
confidence: 99%
“…Ultraviolet (UV) photodetectors based on various organic semiconductors have been achieved for broad applications toward environmental monitoring, biological analysis, image sensing, and optical communication 23–27 . In particular, UV photodetectors based on photoresponsive materials are highly attractive owing to their direct optical and electrical engineering of semiconductor layers, which have been applied for the multifunctional optoelectronic devices 28–31 . For optical operation of UV photodetectors, organic photochromic materials exhibit high optical response and tunable photosensitivity, which can be easily harnessed to modulate physicochemical properties by photovoltaic and photoisomerization effects within an individual system.…”
Section: Introductionmentioning
confidence: 99%